2008
DOI: 10.1126/science.1156121
|View full text |Cite
|
Sign up to set email alerts
|

Human CHN1 Mutations Hyperactivate α2-Chimaerin and Cause Duane's Retraction Syndrome

Abstract: Duane's retraction syndrome (DRS) is a complex congenital eye movement disorder caused by aberrant innervation of the extraocular muscles by axons of brainstem motor neurons. Studying families with a variant form of the disorder (DURS2-DRS), we have identified causative heterozygous missense mutations in CHN1 , a gene on chromosome 2q31 that encodes α2-chimaerin, a Rac guanosine triphosphatase–activating protein (RacGAP) signaling protein previously implicated in the pathfinding of cort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
156
2
7

Year Published

2009
2009
2017
2017

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 157 publications
(171 citation statements)
references
References 28 publications
(35 reference statements)
6
156
2
7
Order By: Relevance
“…Mutations characterized in DURS2 patients such as the G228S mutation confer gain of function on α2-chn, leading to a hyperactivation of downstream signaling pathways (3). OMN neurons transfected with the G228S-α2-chn isoform manifested a higher percentage of collapsed growth cones, per se, than GFP-transfected control neurons (Fig.…”
Section: Sema3a Receptors Plexina1 and Plexina2 Are Expressed By Oculmentioning
confidence: 99%
See 2 more Smart Citations
“…Mutations characterized in DURS2 patients such as the G228S mutation confer gain of function on α2-chn, leading to a hyperactivation of downstream signaling pathways (3). OMN neurons transfected with the G228S-α2-chn isoform manifested a higher percentage of collapsed growth cones, per se, than GFP-transfected control neurons (Fig.…”
Section: Sema3a Receptors Plexina1 and Plexina2 Are Expressed By Oculmentioning
confidence: 99%
“…Neuroimaging studies suggest that DURS2 may involve absence of the abducens concomitant with aberrant innervation of the LR muscle by the OMN, and/or hypoplasia of both the abducens and oculomotor nerves (4,5). We have previously shown that expression of α2-chn forms harboring identified human mutations, in the oculomotor nerves of chicken embryos, leads to characteristic axon guidance defects, suggesting a role for α2-chn in axon pathfinding (3). Such a function for α2-chn is supported by its role in corticospinal tract formation, where it is thought to transduce ephrin-B-EphA4 axon guidance signals (6).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…59,60 It is suggested that human CHN1 mutations alter the development of abducens and, to a lesser extent, oculomotor axons. 60 …”
Section: Duane's Syndromementioning
confidence: 99%
“…4,5,8,9 DRS, klasik olarak etkilenen gözdeki bakış kısıtlılığının yönüne ve abdüksiyon-addüksiyon-daki kısıtlılığın asimetri miktarına göre sınıflan-dırılmaktadır. 1,10 Temel olarak 3 tipi mevcuttur.…”
unclassified